2021
DOI: 10.1186/s12885-021-08382-7
|View full text |Cite
|
Sign up to set email alerts
|

Breast lesions excised via vacuum-assisted system: could we get any clues for B3 lesions before excision biopsy?

Abstract: Background The purpose of this study was to determine the validity of the ultrasound features as well as patient characteristics assigned to B3 (uncertain malignant potential) breast lesions before vacuum-assisted excision biopsy (VAEB). Methods This study population consisted of 2245 women with breast-nodular abnormalities, which were conducted ultrasound-guided VAEB (US-VAEB). Patient’s clinical and anamnestic data and lesion-related ultrasonic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…No reports concerning T2 stage UEBC were found in the literature. Table 1 shows that 69.1% (56/81) of UEBCs occurred in patients aged <50 years, which was higher than 66.7% in a previous study by Zheng et al (17). The difference may have been caused by random error.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…No reports concerning T2 stage UEBC were found in the literature. Table 1 shows that 69.1% (56/81) of UEBCs occurred in patients aged <50 years, which was higher than 66.7% in a previous study by Zheng et al (17). The difference may have been caused by random error.…”
Section: Discussionmentioning
confidence: 62%
“…In the literature, the incidence of UEBC diagnosed by US-VAEB was 1.1–3.4% ( 15 17 ). In our study, it was lower at 0.42%.…”
Section: Discussionmentioning
confidence: 99%
“…For lesions of BI-RADS grade 3 and below, is it safe to perform MWA without histological evaluation? In a study of 2245 women with breast-nodular abnormalities [45], vacuum-assisted excision biopsy was performed to obtain histopathological results. The malignancy rate in BI-RADS grade 3 lesions is only 1.9%, which indicated that the overwhelming majority of BI-RADS grade 3 cases were unnecessarily subjected to biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be considered that MWA is relatively safe even in a very small number of BI-RADS grade 3 malignant lesions, but long-term imaging follow-up observation after MWA is necessary. However, for lesions of BI-RAD grade 4a, the probability of malignancy is greatly increased [45], so it is necessary to obtain histopathological results by CNB or vaccum-assisted (VAB) before microwave ablation. This would bring additional costs to the patient in addition to ablation.…”
Section: Discussionmentioning
confidence: 99%